Implementation of Social Integration in Strengthening Nationalism - Mariatul Kiptiah (International Journal of Science and Society, 2023)
The strength that is able to create social integration is the existence of a mutual agreement in the form of community values, the existence of parties who have the power to instill these values and the need for functional interdependence between community groups so that any established mechanism will be obeyed together in order to achieve common goals. This study aims to identify the description of social integration of society, describe the attitude of nationalism in society, analyze the implementation of social integration in strengthening nationalism, analyze the factors that influence the implementation of social integration in strengthening nationalism. This study uses a meta-analytic approach based on qualitative approach data through in-depth interviews related to social integration in the Tanah Laut Regency area. The results of the research include the social integration of residents in the Tajau Pecah village, which can be seen from the existence of a closer interdependence relationship between the parts so as to create a harmonious atmosphere. A sense of nationalism with an attitude of responsibility, and a feeling of having shared aspirations to improve development in the village of Tajau Pecah. The implementation of social integration in strengthening nationalism in the village of Tajau Pecah, Tanah Laut district, through social interaction which includes inter-ethnic assimilation and communication has been seen in the people of Tajau Pecah village.